Ammonia injection optimization for selective catalytic reduction aftertreatment systems. (July 2021) - Pla, Benjamin; Bares, Pau; Sanchis, Enrique; Aronis, André
This work presents an optimized ammonia injection strategy for the Worldwide Harmonized Light Vehicles Test Cycle and its potential benefits in terms of NO x emissions and ammonia consumption in selective catalytic reduction. An optimization tool based on optimal control was used to improve the ammonia injection in the selective catalytic reduction with different NO x emission limits. This optimal control can be used in two ways: one to minimize NO x emission and another to reduce the ammonia consumption in the selective catalytic reduction. The optimized strategy and the standard ammonia injection strategy were tested and compared on a fully instrumented engine test bench when applied in a Worldwide Harmonized Light Vehicles Test Cycle. The results showed a considerable improvement in the use of the optimization tool. When compared to the standard calibration, the new injection strategy for the same amount of ammonia injection reduced NO x emissions by 13.7%, and for the same NO x concentration emissions 33.5% of ammonia consumption was saved.